The Relationship Between Hip Strength and Postural Stability in Collegiate Athletes Who Participate in Lower Extremity Dominant Sports - Bryce Olsen; Nicholas Freijomil; Jennifer Csonka; Tara Moore; Carolyn Killelea; Mallory S Faherty; Timothy C Sell (North American Sports Medicine Institute, 2021)
# Background Lower extremity (LE) injuries are common across many sports. Both core strength (including hip strength) deficits and poor postural stability have been linked to lower extremity (LE) injury. The relationship between these two characteristics is unknown. # Purpose To explore the relationships between hip strength, static postural stability, and dynamic postural stability. # Study Design Descriptive Cross-Sectional Study # Methods 162 Division I student-athletes (111 males and 51 females) participated in this study. Isometric hip strength was measured using a hand-held dynamometer and both single-leg static (eyes open EO and eyes closed EC) and dynamic postural stability were assessed with a force plate. Pairwise correlations were calculated to examine the relationship between the hip strength variables and the postural stability scores for all subjects and separately for males and females. # Results There were no significant correlations between hip strength and dynamic postural stability for any of the pairwise correlations. Significant, albeit minimal, correlations between EO and EC static postural stability and each of the hip strength variables for all subjects and male subjects (correlation coefficients ranged from -0.19 to -0.34). However, there were only two significant correlations between hip strength and EC static postural stability (hip internal/external rotation) and one for hip strength and EO postural stability (hip internal rotation) found for female subjects (correlation coefficients ranged from -0.28 to -0.31). # Conclusion There was no relationship between isometric hip strength and dynamic postural stability; whereas, there were some relationships between the strength measures and static postural stability. These significant, but minimal correlations were observed in more of the comparisons within the male cohort potentially demonstrating a sex difference. # Level of Evidence 3b